The biological response of Carica papaya leaves extract to saponin reduction (O/W) emulsion on human bronchial epithelium cell (BEAS-2B) - Saiful Irwan Zubairi; Hazreen Omar; Zainun Nurzahim; Nadiah Ramlan (Arabian Journal of Chemistry, 2023)
Carica papaya leaf has a potentially well-known therapeutic effect in accelerating human blood platelet counts against dengue fever and dengue haemorrhagic fever. However, consuming the extract was considered troublesome due to its bitter taste. The fresh papaya leaves were extracted into two types of preparation: a) Fresh Papaya Leaves Extract (FPL) and b) Papaya Leaves with Saponin Reduction Extract (PLSR). This was followed by the determination of the best edible O/W emulsion formulation of both different extracts with virgin coconut oil (VCO) and whey protein (WP) as surfactant. Through Ternary Phase Diagram (TPD), the optimum ratio (w/w) of FPL/PLSR: VCO: WP were 63: 16: 21 and 65: 16: 19 respectively. Both formulas were examined for their physicochemical properties including pH, creaming index (CI), contact angle and droplet size measurement. The human bronchial epithelium cell (BEAS-2B) was treated using both emulsions for 72 hrs of cell growth response (EC50). The result shows that both FPL and PLSR formulations were slightly acidic and exhibited stable emulsion with no creaming formation (CI) up to 24 hrs of storage (25 ℃). Next, FPL emulsion shows 3 times higher wettability and 4 times bigger nanoparticle size than PLSR. These properties can affect the emulsion absorptivity in the targeted cell microenvironment. Remarkably, the BEAS-2B cell viability (%) for each emulsion was relatively elevated within 24 hrs and increased to more than 100 % at 48 and 72 hrs of exposure. This might hugely represent its potential in repairing damaged blood vessels due to dengue haemorrhagic fever. Besides, the EC50 value also indicated low levels of concentration needed to exponentially increase cell growth and safe for dengue fever treatment. For that reason, the recommended effective dosage by the Ministry of Health (Malaysia) (MOH) for both FPL and PLSR emulsions is two tablespoons twice a day for three consecutive days of treatment (equally to the effective dosage of 102 g extract).